Action and Reaction: An Overview of the Ding Dong Relationship between the Colonial Government and the People of Cape Coast (Nordic Journal of African Studies, 2002)
This article looks at the western educated elite of Cape Coast as a factor of change regarding their influence on the traditional political institutions. It also examines the processes by which institutions like the Asafo, a typical traditional military unit, were virtually drawn into national politics as it pertained in Cape Coast. Much as the Asafo retained their fundamental structures as a traditional institution their time-honoured roles took on a more modern dimension. It was a veritable case of the Asafo approaching the precipices of a pressure group, and as it were, being drawn into the colonial political dynamism.